ANALISA MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DALAM KEGAGALAN PROSES BONGKAR MUAT PADA PERUSAHAAN LOGISTIK - Pramudya Audrey Prienycha Islamey; Yesica Novrita Devi; Arie Indartono (Proceeding Maritime Business Management Conference, 2023)
This research was conducted at a logistics service company located in Surabaya and engaged in freight forwarding or commonly referred to as ship cargo expeditions. This logisticsservice company also acts as a Logistics Service Provider (LSP) with several service categories, namely warehousing, stuffing/stripping, ICL, FCL, tally, surveyor, inland transport, general freight forwarding, project & contract logistics, and custom clearance. In all freight forwarding business activities, of course there are several risks of operational failure that causing losses to the company. Therefore, this study uses the Failure Mode and Effect Analysis (FMEA) method to identify and find the risk of failure that occurs that is processed to find the value of the Risk Priority Number (RPN) and the critical risk of operational failure. The results of the study show 8 critical risks and risk management is needed. In handling risk in this company uses 4 strategies, namely immediate action, immediate attention, periodic attention, and annual evaluation.